Assessing pet owner and veterinarian perceptions of need for veterinary compounding services in a community pharmacy setting - Bennett SA; Ruisinger JF; Prohaska ES; Steele KM; Melton BL (Centro de Investigaciones y Publicaciones Farmaceuticas, 2018)
Background: Pets, pet owners (referred to as clients in veterinary medicine and throughout this article), veterinarians, and community pharmacies may all benefit from veterinary compounding services provided in community pharmacies, but the benefits of this service are not well-documented in the literature. Objectives: This study identified perceived benefits and barriers and evaluated the need for veterinary compounding services in community pharmacies; it also evaluated current business practices related to veterinary compounding services. Methods: A cross-sectional survey was administered to three groups: 1) clients who filled a pet prescription at a study pharmacy, 2) clients who had not filled pet prescriptions, and 3) local veterinarians. Eligible participants were 18 or older; clients must have owned a pet in the past five years. The surveys collected demographic information and assessed benefits, barriers, need, and business practices regarding veterinary compounding services. Demographics were evaluated through descriptive statistics. Responses to Likert-scale items were compared between groups using the Mann-Whitney U test. Qualitative responses were assessed for emerging themes. Results: One hundred eighteen clients and 15 veterinarians participated in the study. Seventy-two of 116 clients (62%) and eight of 10 veterinarians (80%) agreed that clients would benefit from veterinary compounds provided in community pharmacies. Only 40% of veterinarians agreed that community pharmacists have the knowledge to compound pet medications, compared to 67% of clients (P=0.010). Similarly, 47% of veterinarians agreed that community pharmacists have the skills to compound pet medications, compared to 72% of clients (P=0.016). Forty-eight of 118 clients (41%) would travel 10 miles or more out of their way for veterinary compounding services at community pharmacies. Conclusions: This study assessed client and veterinarian perceptions of veterinary compounding service benefits, barriers, and need in community pharmacies. Clients identified more opportunities for veterinary compounding services in community pharmacies when compared to veterinarians. Both groups identified a need for veterinary compounding services and agreed community pharmacies providing these services would benefit pets and clients.